Some Results About Self-Adjointness of a Class of Nonlinear Wave Equations - Ibragimov, N.H.; Torrisi, M.; 'a, R. Tracin (Journal of Vibration Testing and System Dynamics, 2026)
In this paper we show some short notes concerned the nonlinear selfadjointess of a class of wave equations. These results, obtained together with prof. Ibragimov between the end of 2017 and January 2018, were the beginning of a wide study that remained incomplete.